O diário de bordo como elemento diferenciador na aprendizagem por projeto, experimental e artística - Branco, Carolina Machado (2017)
This article shares the experience of the making of a graphic diary as a support to illustrate a children's book, with students from the 5th and 6th grades of Colégio Pedro Arrupe, during the Semana do Mar (Sea's Week), a school week dedicated to project-based learning and group work. This graphic diary documents the process of illustration, its graphic regulations (concerning the cover and back-cover), the experimentation of several art supplies, the ideas along the way; this transforms the diary into a graphic research portfolio, highlighting the student's autonomy, self-criticism and reflection